2021
DOI: 10.1136/jclinpath-2020-207280
|View full text |Cite
|
Sign up to set email alerts
|

Real-world biomarker testing rate and positivity rate in NSCLC in Spain: Prospective Central Lung Cancer Biomarker Testing Registry (LungPath) from the Spanish Society of Pathology (SEAP)

Abstract: AimThe aim of this study was to describe the testing rate and frequency of molecular alterations observed in the Lung Cancer Biomarker Testing Registry (LungPath).MethodsA descriptive study of NSCLC biomarker determinations collected from March 2018 to January 2019, from 38 Spanish hospitals, was carried out. Only adenocarcinoma and not otherwise specified histologies were included for epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK), c-ros oncogene 1 (ROS1) and programmed death ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 37 publications
(32 reference statements)
2
31
0
Order By: Relevance
“…The availability of speci c inhibitors of ROS1 and their clinical bene t should lead to test ROS1 rearrangement simultaneously with EGFR mutation and ALK rearrangement in all advanced stage never/light smokers with squamous cell carcinoma and non-squamous NSCLC (6). However, according to the analysis carried out by Salas et al (2021) (15) in Spain in 2018, despite the relatively high testing rate reported in EGFR and ALK in NSCLC (91.4% and 80.1%, respectively), the real-world evidence obtained from the LungPath registry demonstrates that ROS1 and PD-L1 were not determined in a signi cant portion of patients (56.2% and 58.1%, respectively) (15). Based on these authors, the fact that the determination of ROS1 is not always performed in Spain is probably because the determination in some laboratories is sequential, and there is not enough sample material or samples were of poor quality containing insu cient tumor amount to determine all biomarkers (15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The availability of speci c inhibitors of ROS1 and their clinical bene t should lead to test ROS1 rearrangement simultaneously with EGFR mutation and ALK rearrangement in all advanced stage never/light smokers with squamous cell carcinoma and non-squamous NSCLC (6). However, according to the analysis carried out by Salas et al (2021) (15) in Spain in 2018, despite the relatively high testing rate reported in EGFR and ALK in NSCLC (91.4% and 80.1%, respectively), the real-world evidence obtained from the LungPath registry demonstrates that ROS1 and PD-L1 were not determined in a signi cant portion of patients (56.2% and 58.1%, respectively) (15). Based on these authors, the fact that the determination of ROS1 is not always performed in Spain is probably because the determination in some laboratories is sequential, and there is not enough sample material or samples were of poor quality containing insu cient tumor amount to determine all biomarkers (15).…”
Section: Discussionmentioning
confidence: 99%
“…Given the incremental importance of ROS1 testing in guiding the treatment of patients with NSCLC and the fact that ROS1 is an underanalyzed biomarker in comparison to ALK or EGFR in Spain (15), the main objective of our study was to assess if testing ROS1 is a cost-effectiveness strategy in Spain and also to raise the awareness of testing ROS1 according the clinical guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming a conservative estimate of 80% of NSCLC patients (all stages) presenting with advanced-stage disease, annually, these percentages would translate to approximately 14,000, 4800, and 19,400 patients in Italy, Spain, and Germany, respectively. In the Spanish Lung Cancer Biomarker Testing Registry study, ALK was not tested in 20% of cases, and ROS1 was not tested in over 40% of cases [23]. The situation is similar in the USA, as shown by a recent study by the MYLUNG Consortium TM , which demonstrated that most patients (90%) received testing for at least one out of five biomarkers (EGFR, ALK, ROS1, BRAF, and PD-L1) prior to first-line therapy, whereas less than half had testing for all five [24].…”
Section: How Many Patients Miss Out On Biomarker Testing/molecular Di...mentioning
confidence: 99%